2016
DOI: 10.1097/md.0000000000005146
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of tenofovir alafenamide versus tenofovir disoproxil fumarate in antiretroviral regimens for HIV-1 therapy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 34 publications
1
75
0
2
Order By: Relevance
“…Moreover, a meta‐analysis of 2210 patients suggested that changing the HIV regimen to TDF is associated with a reduction in BMD, and switching from TDF to tenofovir alafenamide (TAF) led to an improvement in BMD . A recent double‐blind phase 3 trial of 1733 ART‐naïve HIV‐infected individuals found that a TAF‐based regimen had better virologic efficacy and less impact on BMD compared with a TDF‐based regimen formulated with similar antiretroviral agents . For the moment, it is clear that TAF users had fewer signals of kidney injury compared with TDF users, and decreases in BMD were generally milder, although there is still a significant effect on BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a meta‐analysis of 2210 patients suggested that changing the HIV regimen to TDF is associated with a reduction in BMD, and switching from TDF to tenofovir alafenamide (TAF) led to an improvement in BMD . A recent double‐blind phase 3 trial of 1733 ART‐naïve HIV‐infected individuals found that a TAF‐based regimen had better virologic efficacy and less impact on BMD compared with a TDF‐based regimen formulated with similar antiretroviral agents . For the moment, it is clear that TAF users had fewer signals of kidney injury compared with TDF users, and decreases in BMD were generally milder, although there is still a significant effect on BMD.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with findings of clinical studies assessing TAF-based and NRTI-sparing regimens. E/C/F/TAF was found to be comparable in efficacy to other recommended TDF-or-ABC-based regimens [5,25], while NRTI-sparing regimens were associated with a trend for lower efficacy in most clinical trials compared with other recommended TDFor ABC-based regimens [11,16,18,19,26,27]. Results in patients with viral load < 100 000 copies/mL were consistent with the full analysis and showed similar mean RR with 95% CrI including 1, probably as a consequence of the smaller number of studies which increases the uncertainty and the corresponding 95% CrI.…”
Section: Discussionmentioning
confidence: 92%
“…Nei pazienti HIV-positivi i dettagli eziopatogenetici di tale processo non sono ancora del tutto chiariti (16). Alcuni dati dimostrano come il passaggio a TAF può migliorare la densità minerale ossea rispetto alla prosecuzione di un regime con TDF (17). Miglioramenti nella funzionalità renale e nel metabolismo osseo sono stati riscontrati anche in uno studio relativo allo switch a E/C/F/TAF in pazienti coinfetti HIV/HBV senza alterazioni della funzionalità renale e in un recente lavoro relativo a sicurezza ed efficacia a 48 settimane dello switch a E/C/F/TAF in pazienti monoinfetti HIV con insufficienza renale da lieve a caso clinico Figura 1.…”
Section: Discussioneunclassified